2008
DOI: 10.1177/070674370805300507
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Treatments: Single and Multiple Daily Dosing

Abstract: According to the presented data, it could be reasonable to use lithium as a single evening dose in patients who can tolerate this schedule because no studies have suggested any benefit from administration of multiple daily doses. Possible advantages of single daily dosing, especially in improved compliance, could not be veiled by disadvantages of transient and mild postabsorptive side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…When lithium is administered, patients may experience adverse effects that correlate with the peak serum concentrations of the drug, such as gastrointestinal disturbances. 9 Historically, it was believed that administering MDD of lithium would reduce the peak serum levels and therefore minimize these effects. Other proposed benefits of MDD and of SR preparations include maintaining a more consistent serum level of lithium, theorized to improve prophylactic efficacy by preventing subtherapeutic trough levels.…”
Section: Limitationsmentioning
confidence: 99%
“…When lithium is administered, patients may experience adverse effects that correlate with the peak serum concentrations of the drug, such as gastrointestinal disturbances. 9 Historically, it was believed that administering MDD of lithium would reduce the peak serum levels and therefore minimize these effects. Other proposed benefits of MDD and of SR preparations include maintaining a more consistent serum level of lithium, theorized to improve prophylactic efficacy by preventing subtherapeutic trough levels.…”
Section: Limitationsmentioning
confidence: 99%
“…[37] Interestingly, it has been recently suggested that the administration of a single daily dose may be a viable option that in fact confers advantages with respect to achieving greater compliance and staving off long-term renal damage. [55] Therefore, current plasma lithium concentration recommendations for initiating treatment and prophylaxis, although overlapping, differ significantly (figure 1) and optimal dosing remains a contentious issue.…”
Section: Lithium Dosingmentioning
confidence: 99%
“…Lithium can be given as a single daily dose, usually shortly before bedtime or alternatively every 8-12 h. There has been a recent shift toward SDD, because it may increase compliance and minimize renal adverse effects [105,110]. While in theory SDD could lead to breakthrough symptoms prior to the next dose and result in increased adverse effects due to transient higher peak plasma concentrations compared with multiple daily dosing (MDD), which creates more constant plasma concentrations [105], there is little evidence to support these notions.…”
Section: Dosing and Duration Of Treatment Dosingmentioning
confidence: 99%
“…MDD was associated with significantly more urinary frequency than SDD at day 21 (p = 0.008) and 42 (p = 0.017) [111]. Recent reviews have not demonstrated reduced efficacy or increased adverse effects with SDD versus MDD, however, most evidence comes from small retrospective studies [103,110]. There is a need for a large, prospective long-term trial comparing SDD and MDD.…”
Section: Dosing and Duration Of Treatment Dosingmentioning
confidence: 99%
See 1 more Smart Citation